Auditory stimulation with music influences the geometric indices of heart rate variability in men - Silva, Sheila Aparecida F. da [UNESP]; Guida, Heraldo Lorena [UNESP]; Antônio, Ane M. dos Santos [UNESP]; Ferreira, Lucas Lima [UNESP]; Vanderlei, Luiz Carlos M. [UNESP]; Abreu, Luiz Carlos de; Sousa, Fernando H.; Valenti, Vitor Engrácia [UNESP] (My University, 2014)
Background: Chronic classical music was reported to increase parasympathetic activitywhen evaluating heart rate variability (HRV). It is poor in the literature investigation of the acute effects of baroque and heavy metal styles of musical auditory stimulation on HRV. In this study we evaluated the acute effects of relaxant baroque and excitatory heavy metal music on the geometric indices of HRV in healthy men. Method: The study was performed in 12 healthy men between 18 and 30 years old. We excluded persons with previous experience with music instrument and those who had affinity with the song styles. We analyzed the following indices: RRtri, TINN and Poincaré plot (SD1, SD2 and SD1/SD2 ratio). HRV was recorded at rest for ten minutes. Subsequently they were exposed to relaxant baroque or excitatory heavy metal music for five minutes through an earphone. After the first music exposure they remained at rest for more five minutes and them they were exposed again to Baroque or Heavy Metal music (65–80 dB). The sequence of songs was randomized for each individual. Results: The RRTri and SD2 indices were reduced during the heavy metal musical auditory stimulation (p < 0.05). No changes were observed regarding TINN, SD1 and SD1/SD2 ratio (p > 0.05).The qualitative Poincaré plot analysis indicated that during relaxant classical baroque music there was observed a higher beat-to-beat dispersion of RR intervals compared with no music exposure and during excitatory heavy metal musical auditory stimulation, showing higher HRV. Conclusion: We suggest that excitatory heavy metal music acutely decreases global HRV.